Eficácia da loção com óleo de semente de uva à 5% para redução da radiodermatite: ensaio clínico randomizado - Marconato, Cintia da Silva (2024)
This study aimed to evaluate the efficacy of a 5% grape seed oil lotion compared to the nonionic Crodabase CR2 base for reducing radiodermatitis in women with breast cancer. A randomized, triple-blind, parallel clinical trial with a 1:1 allocation ratio was conducted at the Radiotherapy Unit of a teaching hospital in southern Brazil from March 2022 to July 2023. Eligible participants were women aged 18 years or older, indicated for adjuvant or exclusive radiotherapy, and presenting intact skin in the treatment area. Seven evaluations were conducted at baseline (Zero Radiation Dose), and at doses of 10Gy, 20Gy, 30Gy, 40Gy, 50Gy, or more, and at follow-up. The occurrence of radiodermatitis with wet desquamation was set as a stopping rule. Randomization was performed in blocks of random sizes to form the control group (CG), which received the non-ionic Crodabase CR2 base (n=52), and the intervention group (IG), which received the 5% grape seed oil lotion (n=49). Instruments used included the Acute Radiation Morbidity Scoring Criteria, the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30, and the European Organization for Research and Treatment of Cancer Breast Cancer-Specific Quality of Life Questionnaire BR23. Skin moisture and oiliness were evaluated using SkinUp® and photographic records of the irradiated area. Data were analyzed using descriptive and inferential statistics. The study was approved by the Research Ethics Committee (opinion no. 5.230.615) and registered in ReBEC (RBR-446wxd6a). The incidence of radiodermatitis during treatment was 97%, and at followup, it was 85.4% (IG < CG). Radiodermatitis occurred from 10 Gy in both groups. The prevalent symptoms included mild erythema, pruritus, and epilation. Women in the IG had a 2% lower risk of radiodermatitis than those in the CG (RR 0.98; 95% CI 0.86-1.12). The higher risk of radiodermatitis was associated with higher radiation doses received (RR 2.00; 95% CI 1.36- 2.92) and bra size, with a 1% increase for size “M” (RR 1.01; 95% CI 0.81-1.27) and a 6% increase for size “G” (RR 1.06; 95% CI 0.85-1.31). Changes in moisture and oiliness levels corresponded with the occurrence of radiodermatitis, showing imbalance in both groups during treatment. Elasticity was rated as poor in both groups across all evaluations. Women in both the IG and CG reported good overall health and quality of life, both at baseline (81.3±18.3) and at follow-up (84.6±17.2). Quality of life was worse in women experiencing radiodermatitis in both groups, regardless of classification (p<0.05). Analysis of the EORTC BR-23 showed a low score for the sexual pleasure item (Median 50; IQ=8.3-66.7), and the symptoms related to the breast had the highest score (Median=11.1; IQ=8.3-25). In conclusion, the effect of the 5% grape seed oil lotion compared to the non-ionic Crodabase CR2 base was similar in reducing radiodermatitis in women with breast cancer (p>0.05); higher radiation doses were associated with an increased risk of developing radiodermatitis (p<0.05), and quality of life and general health scores remained good throughout the follow-up.